2002
DOI: 10.1029/2001ja900104
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of high‐latitude field‐aligned currents inferred from Ørsted and Magsat observations

Abstract: [1] In this paper we report on field-aligned currents inferred from high-precision three-component geomagnetic field observations made on board the Danish satellite Ørsted over polar regions. Because of a slow drift in local time of the satellite orbit through the ''noon-midnight'' sector, we were able to study the seasonal dependence of the dynamic properties of the dayside and nightside field-aligned current systems over the Northern and Southern Hemispheres. We find an average over-the-pole distance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
97
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 26 publications
39
97
3
1
Order By: Relevance
“…We have also found that the net current intensity of the two-sheet-structure events is correlated with the solar zenith angle (correlation coefficient is 0.52), while that of the three-sheet-structure events is not (correlation coefficient is 0.054). Therefore, our result for the three-sheet-structure events is consistent with the results of Christiansen et al (2002), but our result for the two-sheet-structure events is not.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We have also found that the net current intensity of the two-sheet-structure events is correlated with the solar zenith angle (correlation coefficient is 0.52), while that of the three-sheet-structure events is not (correlation coefficient is 0.054). Therefore, our result for the three-sheet-structure events is consistent with the results of Christiansen et al (2002), but our result for the two-sheet-structure events is not.…”
Section: Discussionsupporting
confidence: 83%
“…The idea of this voltage generation was originally proposed by Stern (1984) for the generation of the R1 current. Christiansen et al (2002) showed that during quiet periods dayside FACs are closed at a given LT in all seasons, that is, irrespective of the solar zenith angle. This is, at least for two sheet structure FAC, inconsistent with our results that the solar zenith angle dependence of the intensity of R1 is more pronounced than that of R2.…”
Section: Discussionmentioning
confidence: 99%
“…Ohtani et al (2005b) examined the seasonal change in the location of dayside FACs using DMSP data and showed a relative difference of up to 5 • between the poleward summer and equatorward winter locations. In contrast to the Oersted results of Christiansen et al (2002), Ohtani et al (2005b) found that the nightside FACs moved equatorward in summer and poleward in winter with a maximum shift of 4 • . These conflicting results were attributed to different definitions of FAC location.…”
Section: Introductionmentioning
confidence: 42%
“…Fujii et al (1981) used TRIAD satellite observations to show that the average latitude of dayside FACs in summer is 1 • -3 • poleward of the average winter location. More recently, Christiansen et al (2002) using magnetometer data from the Oersted spacecraft reported that the average dayside FAC location is shifted poleward in summer relative to winter, decreasing the over-the-pole distance between the daytime and nighttime current systems by 4 • . However, the same analysis of Magsat data showed that the dawn-dusk cross polar cap distance of the Region 1/Region 2 currents had little seasonal dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Maps of FACs in dependence on e.g. season and the Interplanetary Magnetic Field (IMF) have been derived by data from the satellites Dynamics Explorer-2 (e.g., Weimer 2001), Iridium constellation (e.g., Waters et al 2001), Magsat and Ørsted (e.g., Christiansen et al 2002) and CHAMP (e.g., He et al 2012).…”
Section: Discussionmentioning
confidence: 99%